Dominica. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Dominica during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as exports, standards, imports, training, beekeeping, cooperation between the public and private sectors. Finally, work was done on the value chains of chilli peppers, bananas, pineapples, peppers, onions, honey, on safety, through the Codex Alimentarius and on the inclusion of women.